An Alternative Treatment for Non-Vital Deciduous Molars Using Lesion Sterilization and Tissue Repair: Literature Review and Report of Three Cases With One-Year Follow-Up - Razieh Shojaeepour; Mehrnaz Khademi; Sima Joukar; Roya Borna (Negah Institute for Scientific Communication, 2017)
Introduction: An alternative method for the treatment of non-vital deciduous teeth is Lesion Sterilization and Tissue Repair (LSTR) technique in which instead of instrumentation of the root canals and obturating them with Zinc Oxide Eugenol (ZOE), the root canals are treated with a 3-Mix paste.  Case Report: In the current case report, the therapeutic outcomes of LSTR technique are presented in 3 patients with 3-month, 6-month, and 1-year clinical and radiographic follow-ups. The subjects consisted of patients referring to the Department of Pediatric Dentistry, School of Dentistry, Kerman, Iran.  Conclusions: Considering the successful outcomes of this treatment modality that was comparable to the standard pulpectomy procedure and its advantages such as one-visit treatment, no pushing of necrotic debris toward the buds of succedaneous permanent teeth and absence of ZOE in the root canals absorbed at a lower rate compared to the deciduous tooth roots were observed; hence, the technique might be an alternative technique for the standard pulpectomy procedure.